Viewpoint: Botanic Gardens and Place Identity- Informing a more relevant educational practice - Martin Clement (Environmental Association of Southern Africa, 2007)
Botanic gardens through their history and time-honoured practices have become significant holders of place meanings and are often at the centre of cultural landscape issues across the globe. Botanic gardens, especially in the colonial world, now face the challenge of implementing a more relevant course of action that focuses attention on livelihood and environmental justice. The Durban Botanic Gardens is a case in point where these processes are being actively explored through the Garden Window Project. However, this project requires a new approach for actively and meaningfully engaging with people-plant relationships; one that relies on place associations, narratives and the manner in which plants and place identity provide meaningful learning opportunities for people.